Enhancing Conceptual Understanding of Electric Circuit Analysis through the Jigsaw Method: A Quasi-Experimental Study in Senior High Schools - Acquah, Isaac Kwesi (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This study examines the effectiveness of the Jigsaw cooperative learning method in improving Form 1 students' understanding of electric circuit analysis, problem-solving skills, and its impact compared to traditional teaching. Methodology: A quasi-experimental pre-test and post-test design was employed, involving 87 students from Obiri Yeboah SHS and Dadieso SHS. Over a one-week intervention, the Jigsaw method was integrated into regular physics lessons. Data were collected through tests and questionnaires administered before and after the intervention to assess the students’ knowledge and learning experiences. SPSS was used for statistical analysis, evaluating the effectiveness of the Jigsaw method in improving conceptual understanding. Main Findings: The results demonstrated a significant increase in students' comprehension of electric circuits. At Obiri Yeboah SHS, the average score rose from 50.19 (pre-test) to 83.69 (post-test), and at Dadieso SHS, from 46.50 to 86.57. The Jigsaw method not only improved students' understanding of the subject but also enhanced their problem-solving abilities, communication skills, and motivation to learn. Statistical analyses, including t-tests and Cohen’s d, indicated a strong, significant effect size, reinforcing the method’s effectiveness. Novelty/Originality of this study: This study provides compelling evidence of the Jigsaw method’s ability to enhance student performance and deepen conceptual understanding in science education, particularly in electric circuit analysis. The findings underscore the importance of cooperative learning techniques in promoting active participation, peer teaching, and higher levels of student engagement, suggesting that such strategies are critical for fostering more interactive and impactful classroom experiences.